Implementasi Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas X-7 SMA Negeri 9 Surabaya Pada Mata Pelajaran Matematika Materi Statistika - Avelia Putri Syaharani; Anik Kirana; Fitria Indahwati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The success of the learning process is highly desired in school education. One of the key factors in achieving success is the teacher's selection of appropriate methods for delivering the lesson material in class, which contributes to students' learning outcomes. In mathematics instruction, particularly on the topic of Statistics in class X-7 at SMA Negeri 9 Surabaya, the results have been unsatisfactory, with an average score of 59 for the 2023/2024 academic year. Therefore, improvement is needed through the implementation of the Team Assisted Individualization (TAI) cooperative learning model. The subjects of this study are students of class X-7 at SMA Negeri 9 Surabaya for the 2023/2024 academic year, consisting of 36 students. This study involves a mathematics teacher and an observer. The data collection tools used include formative tests, observation sheets for the teacher, students, and group discussion activities, as well as reflection questionnaires on the learning process. Based on the research findings, it can be concluded that the application of the TAI cooperative learning model can improve the learning outcomes of class X-7 students at SMA Negeri 9 Surabaya on the topic of Statistics. This study is expected to encourage teachers to implement the TAI cooperative learning model in Statistics to enhance students' learning outcomes in Mathematics.